EFFECT OF EARLY MOBILIZATION TO URINE RETENTION EVENT POST HERNIOTOMY OPERATION IN RSUD PROF DR SOEKANDAR MOJOSARI - lutfi wahyuni; binarti dwi wahyuningsih (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
EFFECT OF EARLY MOBILIZATION TO URINE RETENTION EVENT POST HERNIOTOMY OPERATION IN RSUD PROF DR SOEKANDAR MOJOSARI By :Lutfi Wahyuni, Binarti Dwi Wahyuningsih Hernia is a problem that can be found in the case of surgery and became the most cases of surgery after appendicitis. Emergency emergency cases can occur if the hernia is sedentary where there has been a blockage in the food channel which eventually the blood vessels caught should be surgery called herniotomy. Many problems arise from surgery and the risk of anesthesia (spinal anesthesia), including the presence of urinary retention events. This study aims to identify the incidence of urinary retention in postoperative herniotomy patients after early mobili- tation. The design used in this study was pre-experimental with a one-shot case study design. The population in this study were all patients who had undergone herniotomy surgery at 2nd grade inpatient room in RSUD Soekandar Mojosari in February 2017 as many as 27 people. Samples were taken using consecutive sampling technique. Data analysis using descriptive analysis. The result of the research showed that in stage 1 of 30 respondents (95%) who experienced urine retention decreased to 9 respondents (30%) in phase 2 subsequently decreased to 2 respondents (6,6%) in stage 3 and at stage 4 there were no respondents experience urinary retention. There is an effect of early mobilization on the incidence of urinary retention with different responses in each respondent. Early mobilization is influenced by physical factors, emotions and age and developmental status. Keywords: Early Mobilization, Urine Retention, Herniotomy EFFECT OF EARLY MOBILIZATION TO URINE RETENTION EVENT POST HERNIOTOMY OPERATION IN RSUD PROF DR SOEKANDAR MOJOSARI By :Lutfi Wahyuni, Binarti Dwi Wahyuningsih Hernia is a problem that can be found in the case of surgery and became the most cases of surgery after appendicitis. Emergency emergency cases can occur if the hernia is sedentary where there has been a blockage in the food channel which eventually the blood vessels caught should be surgery called herniotomy. Many problems arise from surgery and the risk of anesthesia (spinal anesthesia), including the presence of urinary retention events. This study aims to identify the incidence of urinary retention in postoperative herniotomy patients after early mobili- tation. The design used in this study was pre-experimental with a one-shot case study design. The population in this study were all patients who had undergone herniotomy surgery at 2nd grade inpatient room in RSUD Soekandar Mojosari in February 2017 as many as 27 people. Samples were taken using consecutive sampling technique. Data analysis using descriptive analysis. The result of the research showed that in stage 1 of 30 respondents (95%) who experienced urine retention decreased to 9 respondents (30%) in phase 2 subsequently decreased to 2 respondents (6,6%) in stage 3 and at stage 4 there were no respondents experience urinary retention. There is an effect of early mobilization on the incidence of urinary retention with different responses in each respondent. Early mobilization is influenced by physical factors, emotions and age and developmental status. Keywords: Early Mobilization, Urine Retention, Herniotomy EFFECT OF EARLY MOBILIZATION TO URINE RETENTION EVENT POST HERNIOTOMY OPERATION IN RSUD PROF DR SOEKANDAR MOJOSARI By :Lutfi Wahyuni, Binarti Dwi Wahyuningsih Hernia is a problem that can be found in the case of surgery and became the most cases of surgery after appendicitis. Emergency emergency cases can occur if the hernia is sedentary where there has been a blockage in the food channel which eventually the blood vessels caught should be surgery called herniotomy. Many problems arise from surgery and the risk of anesthesia (spinal anesthesia), including the presence of urinary retention events. This study aims to identify the incidence of urinary retention in postoperative herniotomy patients after early mobili- tation. The design used in this study was pre-experimental with a one-shot case study design. The population in this study were all patients who had undergone herniotomy surgery at 2nd grade inpatient room in RSUD Soekandar Mojosari in February 2017 as many as 27 people. Samples were taken using consecutive sampling technique. Data analysis using descriptive analysis. The result of the research showed that in stage 1 of 30 respondents (95%) who experienced urine retention decreased to 9 respondents (30%) in phase 2 subsequently decreased to 2 respondents (6,6%) in stage 3 and at stage 4 there were no respondents experience urinary retention. There is an effect of early mobilization on the incidence of urinary retention with different responses in each respondent. Early mobilization is influenced by physical factors, emotions and age and developmental status. Keywords: Early Mobilization, Urine Retention, Herniotomy EFFECT OF EARLY MOBILIZATION TO URINE RETENTION EVENT POST HERNIOTOMY OPERATION IN RSUD PROF DR SOEKANDAR MOJOSARI By :Lutfi Wahyuni, Binarti Dwi Wahyuningsih Hernia is a problem that can be found in the case of surgery and became the most cases of surgery after appendicitis. Emergency emergency cases can occur if the hernia is sedentary where there has been a blockage in the food channel which eventually the blood vessels caught should be surgery called herniotomy. Many problems arise from surgery and the risk of anesthesia (spinal anesthesia), including the presence of urinary retention events. This study aims to identify the incidence of urinary retention in postoperative herniotomy patients after early mobili- tation. The design used in this study was pre-experimental with a one-shot case study design. The population in this study were all patients who had undergone herniotomy surgery at 2nd grade inpatient room in RSUD Soekandar Mojosari in February 2017 as many as 27 people. Samples were taken using consecutive sampling technique. Data analysis using descriptive analysis. The result of the research showed that in stage 1 of 30 respondents (95%) who experienced urine retention decreased to 9 respondents (30%) in phase 2 subsequently decreased to 2 respondents (6,6%) in stage 3 and at stage 4 there were no respondents experience urinary retention. There is an effect of early mobilization on the incidence of urinary retention with different responses in each respondent. Early mobilization is influenced by physical factors, emotions and age and developmental status. Keywords: Early Mobilization, Urine Retention, Herniotomy EFFECT OF EARLY MOBILIZATION TO URINE RETENTION EVENT POST HERNIOTOMY OPERATION IN RSUD PROF DR SOEKANDAR MOJOSARI By :Lutfi Wahyuni, Binarti Dwi Wahyuningsih Hernia is a problem that can be found in the case of surgery and became the most cases of surgery after appendicitis. Emergency emergency cases can occur if the hernia is sedentary where there has been a blockage in the food channel which eventually the blood vessels caught should be surgery called herniotomy. Many problems arise from surgery and the risk of anesthesia (spinal anesthesia), including the presence of urinary retention events. This study aims to identify the incidence of urinary retention in postoperative herniotomy patients after early mobili- tation. The design used in this study was pre-experimental with a one-shot case study design. The population in this study were all patients who had undergone herniotomy surgery at 2nd grade inpatient room in RSUD Soekandar Mojosari in February 2017 as many as 27 people. Samples were taken using consecutive sampling technique. Data analysis using descriptive analysis. The result of the research showed that in stage 1 of 30 respondents (95%) who experienced urine retention decreased to 9 respondents (30%) in phase 2 subsequently decreased to 2 respondents (6,6%) in stage 3 and at stage 4 there were no respondents experience urinary retention. There is an effect of early mobilization on the incidence of urinary retention with different responses in each respondent. Early mobilization is influenced by physical factors, emotions and age and developmental status. Keywords: Early Mobilization, Urine Retention, Herniotomy EFFECT OF EARLY MOBILIZATION TO URINE RETENTION EVENT POST HERNIOTOMY OPERATION IN RSUD PROF DR SOEKANDAR MOJOSARI By :Lutfi Wahyuni, Binarti Dwi Wahyuningsih Hernia is a problem that can be found in the case of surgery and became the most cases of surgery after appendicitis. Emergency emergency cases can occur if the hernia is sedentary where there has been a blockage in the food channel which eventually the blood vessels caught should be surgery called herniotomy. Many problems arise from surgery and the risk of anesthesia (spinal anesthesia), including the presence of urinary retention events. This study aims to identify the incidence of urinary retention in postoperative herniotomy patients after early mobili- tation. The design used in this study was pre-experimental with a one-shot case study design. The population in this study were all patients who had undergone herniotomy surgery at 2nd grade inpatient room in RSUD Soekandar Mojosari in February 2017 as many as 27 people. Samples were taken using consecutive sampling technique. Data analysis using descriptive analysis. The result of the research showed that in stage 1 of 30 respondents (95%) who experienced urine retention decreased to 9 respondents (30%) in phase 2 subsequently decreased to 2 respondents (6,6%) in stage 3 and at stage 4 there were no respondents experience urinary retention. There is an effect of early mobilization on the incidence of urinary retention with different responses in each respondent. Early mobilization is influenced by physical factors, emotions and age and developmental status. Keywords: Early Mobilization, Urine Retention, Herniotomy